An Existential Ecofeminism and a Renewed Critical Theory of Nature: An Imagined Dialogue between Simone de Beauvoir and Jürgen Habermas - Morgan, Marcia (Universidade Estadual de Campinas, 2017)
Simone de Beauvoir has been commonly criticized for separating women from nature and attempting to make women “like men”, as beings that dominate nature. I defend Beauvoir’s existential concept of freedom as a non-sovereign relationship with nature. I then use the existential model constructed from my defense of Beauvoir as a framework with which to critique and engage Jürgen Habermas’ 2001 intervention against liberal eugenics. My critique of Habermas is important because I would like to explore a renewed critical theory of nature from the perspective gained by an existential ecofeminism.